Peranan Emas Dan Crypto Hedge Fund Dalam Meningkatkan Kinerja Indeks Portofolio Indeks Saham LQ45, JII, High Dividend, Dan Sri-Kehati - Jenifer Christiani Bowa; Robiyanto Robiyanto (Magister Manajemen STIE Bank BPD Jateng, 2023)
This research was conducted to determine the role of gold and crypto hedge funds in improving the performance of stock index portfolios. The stock index portfolio used consists of the LQ45, JII, High Dividend, and SRI-KEHATI indices. The purpose of this study is to analyze the role of gold and crypto hedge funds in improving the performance of stock index portfolios for the 2019-2021 period rather than investing in portfolios made up of stock indexes only. This study uses the Naive method and measures portfolio performance based on the Sharpe Index, Treynor Index, Jensen Index, Sortino Ratio, and Omega Ratio. This study concludes that the formation of a portfolio with the role of gold and crypto hedge funds can improve the performance of stock indexes using the calculation results of the Naive Diversification model in the period January 1 2019 to December 30 2021. In general it is found that portfolios formed with gold and crypto hedge funds as value better hedged than a portfolio formed without a hedge